Quatification of carrageenan in gracilaria cf. Manilensis (Rhodophyta) exposed to different salinities and PH using attenuated total reflection-fourier transform infrared spectroscopy (ATR-FTIR) - Zakaria, Najibah; Mohammad Noor, Normawaty; Susanti, Deny; Mukai, Yukinori (2018)
Carrageenan is a gel-forming and viscosifying polysaccharides that is commonly found in red algae (Rhodophyta). Previous studies indicate that carrageenan content in the seaweed can be influenced by different environmental conditions. Therefore, in this study, Graciliaria cf. manilensis, a red algae, was exposed at 500 lux under different salinities (15, 20, 25 and 30 psu) and pH (7.6, 7.8 and 8.0) in laboratory condition and carrageenan was determined qualitatively and quantitatively using Attenuated Total Reflection-Fourier Transform Infrared Spectroscopy (ATR-FTIR). Qualitatively, kappa carrageenan was found in most of the Gracilaria samples. Quantitatively, kappa carrageenan was detected ranging from 29.74 ± 7.24 to 56.97 ± 4.03 % (w/w) with the highest carrageenan content was determined at low salinity and slightly neutral pH (15 psu and pH 7.6). . However, G. cf. manilaensis collected from farm and used as a control did not showed the presence of carrageenan. This suggests that different environmental conditions play an important role in determining the carrageenan type and content. This is important as carrageenan is widely used in food, medicinal, pharmaceutical and industrial applications. Furthermore, G. cf. manilensis can be an alternative source of carrageenan besides available sources which is quite limited, to fulfill the high demand of carrageenan.